Analisis Praanggapan pada Podcast Mata Najwa Episode “Kuliah, Kerja, dan Kenyataan” dalam Perspektif Pragmatik - Aisyah Putri; Hosniyeh Hosniyeh (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Based on the analysis results, it can be concluded that the discourse in the Mata Najwa podcast episode “Kuliah, Kerja, dan Kenyataan” (College, Work, Reality) contains six types of presuppositions according to George Yule's classification, namely existential, factual, non-factual, lexical, structural, and counterfactual presuppositions. Among the data analyzed, existential and factual presuppositions are the most dominant. The dominance of these two types of presuppositions shows that the discussion in this podcast relies heavily on assumptions about the existence of social entities and conditions that are taken for granted by the speakers and their interlocutors, such as students, college graduates, educational institutions, and the realities of the working world. This suggests that the speakers construct their arguments and views by drawing on collective experiences and the audience's general knowledge. Thus, this study confirms that presuppositions play an important role in effective communication, clarifying the meaning of speech and deepening the discourse in podcasts, a medium for public discussion that is dialogical, reflective, and contextual. As a recommendation, further research is suggested to examine other episodes or different discourse media in order to obtain a more comprehensive understanding of the patterns of assumption use. In addition, further research can also use a critical discourse analysis approach to examine. As a recommendation, further research is advised to examine other episodes or different discursive media in order to obtain a more comprehensive understanding of the patterns of presupposition use. In addition, future research could use a critical discourse analysis approach to examine the role of preconceptions in shaping ideology and power relations in media discourse, or apply a contextual-pragmatic approach to understand the relationship between preconceptions and the social context and communication situation.